Loasaceae endémicas del Perú - Rodriguez, Eric (2006)
The Loasaceae are represented in Peru by eight genera and around 112 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly herbs. Here we recognize 59 species and 10 infra-specific taxa in five genera as Peruvian endemics. Nasa is the genus with the largest number of endemic species. These endemic taxa are found in the Mesoandean, Humid and Dry Puna, and Very Humid Montane Forest regions, between 1400 and 4700 m elevation. Ten of these taxa have been found in the Peruvian protected areas system.